Hidden Human Capital : Psychological Empowerment and Adolescent Girls' Aspirations in India - Roy, Sanchari; Morton, Matthew; Bhattacharya, Shrayana (World Bank, Washington, DC, 2016)
This paper studies the role of social-emotional or psychological capital in determining the education and employment aspirations of adolescent girls and young women in India. The study finds that girls' self-efficacy and mental health are important determinants of their educational and employment aspirations, suggesting that these hidden forms of human capital may serve as critical targets for interventions aiming to alter girls' educational and economic trajectories. The study also identifies factors that correlate with girls' level of self-efficacy, and finds that an "enabling" and supportive family and community environment appears to be important.